Trait‐similarity and trait‐hierarchy jointly determine fine‐scale spatial associations of resident and invasive ant species. Issue 4 (21st December 2020) - Wong, Mark K. L.; Tsang, Toby P. N.; Lewis, Owen T.; Guénard, Benoit
Abstract : Interspecific competition, a dominant process structuring ecological communities, is influenced by species' phenotypic differences. Limiting similarity theory holds that species with similar traits should compete intensely ('trait‐similarity'). In contrast, competing theories including modern coexistence theory emphasize that species with traits conferring competitive advantages should outcompete others ('trait‐hierarchy'). Either or both of these mechanisms may drive competitive exclusion, but their relative importance and interacting effects are rarely studied. Here, we explore empirically whether trait‐similarity and trait‐hierarchy can explain fine‐scale spatial associations observed between invasive and native ant species in a tropical assemblage. We find that pairwise co‐occurrences between the invasive red imported fire ant Solenopsis invicta and 28 other species across relatively homogenous grasslands can be explained largely by an interaction of trait‐similarity and trait‐hierarchy in a single morphological trait, relative pronotum width. Specifically, higher trait‐hierarchy values are associated with negative co‐occurrences; however, these effects are counteracted when species are increasingly dissimilar in their trait ranges. These findings are consistent with the notion that limiting similarity and competitive hierarchies are interactive rather than discrete mechanisms driving competitive exclusion.